New records of Pseudopaludicola pocoto Magalhães,Loebmann,Kokubum,Haddad & Garda,2014 (Amphibia: Anura: Leptodactylidae) in the Caatinga Biome,Brazil - Lantyer-Silva, Amanda S.F. [UNESP]; Matos, Marlla A.; Gogliath, Melissa; Marciano, Euvaldo; Nicola, Patrícia A. (Pensoft Publishers, 2016)
We provide new records of Pseudopaludicola pocoto Magalhães,Loebmann,Kokubum,Haddad & Garda,2014 in the Caatinga Biome in the states of Paraíba and Pernambuco,which fill a distribution gap in this species’ range.
Keywords: Geographic distribution; Paraíba state; Pernambuco state; Range extension; South america